A compositional analysis of native and decellularized porcine nasal septum cartilage - Tluczynski, Katharina; Breiter, Roman (Xenotransplantation, 2022)
Objectives: Decellularization of porcine septum cartilage is necessary for its application as xenogenic replacement material. The aim of this study was to investigate spatial differences of structure and composition in the whole native and decellularized porcine nasal septum. Subsequently, the results shall be compared with studies of human nasal septum. Methods: Ten porcine nasal septa were divided into six regions from caudal to cephalic and four regions from dorsal to ventral to create a grid of 24 approximately equal segments. All segments of five septal cartilages were decellularized separately by a wet chemical multistep procedure. The segments were analyzed to determine quantitative amounts of total collagen, chondrocytes, and sulfated glycosaminoglycans (sGAG). Results: The distribution of cell number showed no significant differences between the individual regions. For the distribution of collagen and sGAG, no significant differences could be identified from caudal to cephalic, both in native and decellularized tissue. From dorsal to ventral, native and decellularized nasal septum showed significant differences between individual regions. In native septum, linear regression analysis indicated a decreasing collagen and an increasing sGAG content from dorsal to ventral. After decellularization, an increasing collagen and a decreasing sGAG content was detected. Conclusion: The results of this study showed slightly but significant differences in the distribution of collagen and sGAG from dorsal to ventral. From caudal to cephalic, no differences could be observed. Compared to human, nasal septum differences in cell, collagen, and sGAG content were detected. Despite this, human and porcine nasal septum showed similar distributions and a consistently inverse linearity of collagen and sGAG content. Nevertheless, the midcaudal and midcephalic regions showed the highest porosity and a high stability and thus offer the best conditions for the revitalization of porcine tissue by human cells.
CRIS-Team Scopus Importer:2022-09-30
Keywords: cartilage tissue engineering; decellularized cartilage; distribution; nasal septum; porcine septal cartilage

Decellularized xenogenic meniscus as a replacement for meniscal tissue - Körber, Ludwig; Mauer, Julia; Rösch, Rebecca; Tluczynski, Katharina; Schwarz, Silke; Rotter, Nicole; Buchholz, Rainer; Breiter, Roman (European Cells and Materials, Vol. 31, Suppl. 1, 2016)

Experimental approach to nasal septal cartilage regeneration with adipose tissue-derived stem cells and decellularized porcine septal cartilage - Kuhlmann, Constanze; Schenck, Thilo Ludwig; Tluczynski, Katharina; Aszodi, Attila; Metzger, Philipp; Giunta, Riccardo; Wiggenhauser, Paul Severin (Xenotransplantation, 2020)
Background: Cartilage shortage is a major problem in facial reconstructive surgery. Prior studies have shown that decellularized porcine nasal septal cartilage (DPNC) seeded with primary human nasal chondrocytes enabled cartilage regeneration and showed potential as a replacement material for nasal cartilage. Since adipose tissue-derived stem cells (ASCs) are easily accessible and almost abundantly available, they appear to be a promising alternative to limited chondrocytes making the combination of DPNC and ASCs a feasible approach towards clinical translation. Thus, this study was intended to investigate the interactions between ASCs and DPNC in an in vitro model. Methods: DPNCs were seeded and 3D-cultured with primary human ASCs that were priorly characterized with trilineage differentiation and flow cytometry. Cell vitality and proliferation were evaluated by Live-Dead, alamarBlue, and PicoGreen assays. Chondrogenic differentiation was examined by DMMB assay and cryosectioning-based histology. Cell invasion within DPNC was visualized and quantified by fluorescent histology (DAPI, Phalloidin). Results: ASCs showed good adherence to DPNC and Live-Dead assay proved their viability over 2 weeks. AlamarBlueassay showed an increase in metabolic activity compared to 2D cultures, and PicoGreen assay demonstrated an increase of cell number within DPNC over time. Biochemical assays and histology added evidence of chondrogenic differentiation of 3D-cultured ASCs under the influence of chondrogenic induction medium. Fluorescent image analysis showed a significant increase of cell-occupied areas of scaffolds over time (P <.05). Conclusions: DPNC scaffolds provided a suitable environment for ASCs that allowed good cell vitality, high proliferation, and chondrogenic differentiation. Thus, the use of ASCs and DPNC yields a promising alternative to the use of primary human chondrocytes. For facial cartilage tissue engineering, we regard ASCs as an attractive alternative to human nasal chondrocytes due to their better accessibility and availability. Further research will be necessary to determine long-term effects and in vivo outcomes of ASCs and DPNC in cartilage regeneration of the face.
CRIS-Team Scopus Importer:2020-12-25
Keywords: adipose tissue-derived stem cells; cartilage regeneration; decellularized porcine nasal cartilage; extracellular matrix; facial reconstruction

Revitalisation of a decellularised xenogenic meniscus implant by cells from human synovial membrane - Tluczynski, Katharina; Körber, Ludwig; Schwarz, Silke; Rotter, Nicole; Buchholz, Rainer; Breiter, Roman (European Cells and Materials, Vol. 31, Suppl. 1, 2016)